ESTIMASI AIR MAMPU CURAH MENGGUNAKAN DATA MODIS SEBAGAI INFORMASI CUACA SPASIAL DI PULAU JAWA - Parwati Setiawan; Agus Hidayat; Totok Sugiharto; - Hasnaeni (Indonesian National Institute of Aeronautics and Space (LAPAN), 2006)
Study on the utilization of satellite data for precipitable water vapor over Java Island has been done. MODIS (Moderate Resolution Imaging Spectroradiometer)data of TERRA/AQUA satellite are used to estimate the precipitable water. As one of the dynamic atmospheric parameter, the precipitable water data is able to indicate the dryness or wetness of a certain region. Such data can be devired from MODIS data at the wavelength range of 0.865, 1.24, 0.905, 0.936, and 0.940 um. Verification of precipitable water from MODIS data is done by using radiosodle data at 2 climatology station in Java Island (Jakarta and Surabaya). The verification result illustrate that the standart deviation between MODIS precipitable water and radiosonde data for the period of August-October 2004, the standard deviation is ± 1.6 cmand the correlation coefficient is 0.88. In addition, It is found that the correlation between the MODIS precipitable water and the altitude is significantly polynomial model. Beside that, the precipitable water tends to decrease along with the increase of the altitude at 0-2000 m above the sea level. The precipitable water in West Java is higher than in East Java, both in dry season and in rainy season. This condition can explain why the climate in West Java more wet than in East Java. We hope this research can be useful for spatial weather information in large area in real time.